Oxygen for end-of-life lung cancer care: managing dyspnea and hypoxemia. (October 2013) - Tiep, Brian; Carter, Rick; Zachariah, Finly; Williams, Anna C; Horak, David; Barnett, Mary; Dunham, Rachel
Oxygen is commonly prescribed for lung cancer patients with advancing disease. Indications include hypoxemia and dyspnea. Reversal of hypoxemia in some cases will alleviate dyspnea. Oxygen is sometimes prescribed for non-hypoxemic patients to relieve dyspnea. While some patients may derive symptomatic benefit, recent studies demonstrate that compressed room air is just as effective. This raises the question as to whether to continue their oxygen. The most efficacious treatment for dyspnea is pharmacotherapy–particularly opioids. Adjunctive therapies include pursed lips breathing and a fan blowing toward the patient. Some patients may come to require high-flow oxygen. High-flow delivery devices include masks, high-flow nasal oxygen and reservoir cannulas. Each device has advantages and drawbacks. Eventually, it may be impossible or impractical to maintain a SpO2 > 90%. The overall goal in these patients is comfort rather than a target SpO2 . It may eventually be advisable to remove continuous oximetry and transition focus to pharmacological management to achieve patient comfort.